The Most Traversed Bridge: A Reconsideration of Elite and Popular Religion in Late Medieval Ireland* - Ryan, Salvador (Studies in church history, 2006)
Recent years have witnessed the study of late medieval religion change and develop almost beyond recognition. In particular, the phenomenon of ‘popular’ or ‘traditional’ religion has increasingly been placed under the microscope. A succession of studies has questioned the view that an unbridgeable chasm existed between the religious sensibilities of the privileged echelons of society (the higher clergy and members of the nobility) and those of the lower social orders. The apparent sea-change in our understanding of how many expressions of belief and devotion were shared across a wide social spectrum has led, however, to more questions than answers.